2013
DOI: 10.1155/2013/157529
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Culture Bioprocess ofMethanothermobacter thermautotrophicusto Upgrade Digester Biogas by CO2-to-CH4Conversion with H2

Abstract: We optimized and tested a postbioprocessing step with a single-culture archaeon to upgrade biogas (i.e., increase methane content) from anaerobic digesters via conversion of CO2 into CH4 by feeding H2 gas. We optimized a culture of the thermophilic methanogen Methanothermobacter thermautotrophicus using: (1) a synthetic H2/CO2 mixture; (2) the same mixture with pressurization; (3) a synthetic biogas with different CH4 contents and H2; and (4) an industrial, untreated biogas and H2. A laboratory culture with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 20 publications
3
90
0
2
Order By: Relevance
“…In this respect, one has to also keep in mind that enriching hydrogenotrophic methanogenic microbial cultures might require a pre-adaption period in order to make the culture fully acclimated to special fermentation temperatures and/or H 2 /CO 2 gassing rates, a modus operandi which is not required for pure culture of microorganisms. The results of above presented studies also show that a fully acclimated hydrogenotrophic methanogenic enrichment culture can sustain overpressure conditions and is furthermore capable of microbiological biogas upgrading as well as of achieving high MERs [28], a finding, in controversy to discussions found elsewhere [30]. Eventually, during experiments applying a monoculture of hydrogenotrophic methanogens it has been shown, that an increase of the pressure inside the bioreactor will elevate the MER, which is a consequence of increasing the maximum solubility of gasses inside the liquid phase [23,24,30].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…In this respect, one has to also keep in mind that enriching hydrogenotrophic methanogenic microbial cultures might require a pre-adaption period in order to make the culture fully acclimated to special fermentation temperatures and/or H 2 /CO 2 gassing rates, a modus operandi which is not required for pure culture of microorganisms. The results of above presented studies also show that a fully acclimated hydrogenotrophic methanogenic enrichment culture can sustain overpressure conditions and is furthermore capable of microbiological biogas upgrading as well as of achieving high MERs [28], a finding, in controversy to discussions found elsewhere [30]. Eventually, during experiments applying a monoculture of hydrogenotrophic methanogens it has been shown, that an increase of the pressure inside the bioreactor will elevate the MER, which is a consequence of increasing the maximum solubility of gasses inside the liquid phase [23,24,30].…”
Section: Discussionmentioning
confidence: 64%
“…The results of above presented studies also show that a fully acclimated hydrogenotrophic methanogenic enrichment culture can sustain overpressure conditions and is furthermore capable of microbiological biogas upgrading as well as of achieving high MERs [28], a finding, in controversy to discussions found elsewhere [30]. Eventually, during experiments applying a monoculture of hydrogenotrophic methanogens it has been shown, that an increase of the pressure inside the bioreactor will elevate the MER, which is a consequence of increasing the maximum solubility of gasses inside the liquid phase [23,24,30]. Hence, by applying overpressure an increase of the MER could be achieved, if a hydrogenotrophic and methanogenic enrichment culture would be utilized for ex situ microbiological biogas upgrading.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The same research team observed that the H2 mass transfer is the main limitation in this process. The higher is the H2 retention time, the higher is the CH4 conversion efficiency [7]. Methane production of 20 m 3 CH4/m 3 reactor/day is achievable with low H2 remaining in the effluent gas (<10 %).…”
Section: Injection In a Bioreactor With The Biogas (Alternative 2)mentioning
confidence: 99%